Coming out - Steel, Danielle (New York : Delacorte Press, 2006)
When Olympia Rubinstein's twin daughters are invited to a debutante ball, chaos erupts. One twin and Olympia's ex-husband are anxious to go, while the other twin and Olympia's current husband refuse to go.
Keywords: Twins -- Fiction; Debutante balls -- New York (State) -- New York -- Fiction; Coming out (Sexual orientation) -- Fiction; Domestic fiction